2015
DOI: 10.5430/irhe.v1n1p125
|View full text |Cite
|
Sign up to set email alerts
|

Factors in the Adjustment and Academic Achievement of College Students with Learning Disabilities in Israel

Abstract: The number of students with learning disabilities (LD) who attend postsecondary education has increased steadily over the past 20 years. This study examines the contribution of internal (academic self-efficacy and attachment style) and external (social support and institutional support) factors to the adjustment and achievement of students with LDs in the academic setting. Participants were 674 students from 24 institutions of higher education in Israel. The experimental group (n = 338) consisted of students w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…We investigated the inclusive analysis, which revealed that challenges and factors influencing first-year students' academic adjustment processes. First-year students face a multitude of challenges, including poor academic performance, which aligns with Krisher and Shechtman [61] on learning disabilities, language barriers aligned with foreign language speaking anxiety revealed by Batiha and Mustaffa [62], financial constraints aligned with Garwe and Maganga [63] on the effect of student financial constraints, university non-completion rates, urban lifestyle adjustments align with Liang et al [64], social integration and independent living align with [11], [13] and [17]. Meanwhile, various factors, including social support, academic preparedness, and access to resources, influence first-year students' adjustment to university life, aligning with the findings [12].…”
Section: Discussionmentioning
confidence: 61%
“…We investigated the inclusive analysis, which revealed that challenges and factors influencing first-year students' academic adjustment processes. First-year students face a multitude of challenges, including poor academic performance, which aligns with Krisher and Shechtman [61] on learning disabilities, language barriers aligned with foreign language speaking anxiety revealed by Batiha and Mustaffa [62], financial constraints aligned with Garwe and Maganga [63] on the effect of student financial constraints, university non-completion rates, urban lifestyle adjustments align with Liang et al [64], social integration and independent living align with [11], [13] and [17]. Meanwhile, various factors, including social support, academic preparedness, and access to resources, influence first-year students' adjustment to university life, aligning with the findings [12].…”
Section: Discussionmentioning
confidence: 61%
“…Studies that have compared students with disabilities to students without disabilities in terms of the four domains of academic, social, personal-emotional, and institutional adjustments have revealed that students with disabilities display poorer adjustments on the social, personal-emotional, and institutional adjustment subscales than students without disabilities (Adams and Proctor, 2010;Lipka et al, 2020). In particular, students with LD/ADHD have been reported to have lower adjustment scores and academic success rates than students without LD/ADHD (Krisher and Shechtman, 2016;Lipka et al, 2020).…”
Section: Adjustment To Higher Education Among Students With Ld or Adhdmentioning
confidence: 99%
“…Demanding academic, financial constrain as well as interpersonal and intrapersonal relationship are among the major causes of stress (Esiah-Donkoh, & Yelpier, 2011) University students therefore have a unique cluster of stressful experience and stressors. All this can add to normal stress of life and begin to have a negative effect on students (Krisher & Shechtman, 2016). University education life is one of the most exciting milestone of young people (Azilla et al, 2015).…”
Section: Introductionmentioning
confidence: 99%